Optimal Configuration of Electricity-Hydrogen Hybrid Energy Storage System Based on Multi-objective Artificial Hummingbird Algorithm - Zijing LU; Zishou LI; Xiangguo GUO; Bo YANG (Zhongguo dianli)
Through the combination of hydrogen energy storage system and battery energy storage system, the long-term and fast energy conversion can be achieved and the impact of increasing penetration of distributed generation on the stability of distribution network can also be reduced. Considering the economic and technical requirements of hybrid electric-hydrogen energy storage system connected to distribution network, a multi-objective optimal configuration model of hybrid electric-hydrogen energy storage system is established to minimize the life cycle cost, voltage fluctuation and net load fluctuation of distribution network. The multi-objective artificial hummingbird algorithm based on Pareto is used to solve the planning scheme and then compared with the multi-objective particle swarm optimization and multi-objective atomic orbital search algorithm. Finally, the model based on the extended IEEE-69 bus standard test system is solved. The simulation results show that with the proposed multi-objective artificial hummingbird algorithm Pareto frontier can be obtained with better solution set quality. The resulting hybrid energy storage system configuration scheme can improve the voltage quality and load level of distribution network while taking into account the economic benefits. Compared with the energy storage system of exclusive battery configuration, the application of electric-hydrogen hybrid energy storage system can improve the distribution network net load fluctuation and voltage fluctuation by 21.02% and 16.66% respectively, which has verified the effectiveness and outstanding performance of the optimal configuration method proposed in this paper.